2022
DOI: 10.1038/s41467-022-27981-x
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the reaction mechanism behind CoO as active phase for CO2 hydrogenation

Abstract: Transforming carbon dioxide into valuable chemicals and fuels, is a promising tool for environmental and industrial purposes. Here, we present catalysts comprising of cobalt (oxide) nanoparticles stabilized on various support oxides for hydrocarbon production from carbon dioxide. We demonstrate that the activity and selectivity can be tuned by selection of the support oxide and cobalt oxidation state. Modulated excitation (ME) diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) reveals that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 81 publications
4
91
0
Order By: Relevance
“…Interestingly, Have et al demonstrated that H 2 activation routes differ depending on the cobalt oxidation state in CO 2 -based Fischer–Tropsch synthesis. In particular, they showed that while H 2 is adsorbed dissociatively over metallic cobalt, cobalt oxide follows a H 2 -assisted pathway . In addition to the potential influence of acidity as previously discussed, the observed shift from mainly terminal to close-to-terminal C–C bond cleavage in polyolefin hydrogenolysis over Co/ZSM-5 might stem from the preferential stabilization of oxidized cobalt phases by the zeolite that are different from those observed for bulk Co 3 O 4 or other supports under reductive conditions.…”
mentioning
confidence: 88%
“…Interestingly, Have et al demonstrated that H 2 activation routes differ depending on the cobalt oxidation state in CO 2 -based Fischer–Tropsch synthesis. In particular, they showed that while H 2 is adsorbed dissociatively over metallic cobalt, cobalt oxide follows a H 2 -assisted pathway . In addition to the potential influence of acidity as previously discussed, the observed shift from mainly terminal to close-to-terminal C–C bond cleavage in polyolefin hydrogenolysis over Co/ZSM-5 might stem from the preferential stabilization of oxidized cobalt phases by the zeolite that are different from those observed for bulk Co 3 O 4 or other supports under reductive conditions.…”
mentioning
confidence: 88%
“…While our data show that the state of the surface of metallic cobalt is not modified by varying feed composition in terms of CO/CO 2 proportions, we need to stress that some CoOx phases may still have been present under reaction conditions. Those were shown to lead mostly to methane formation 12 . These authors proposed that two reaction pathways occurred, one through CO(ads) on metallic cobalt and one through carbonate/formate on CoOx.…”
Section: /13mentioning
confidence: 99%
“…Metallic cobalt is often considered as the most active phase during CO and CO 2 hydrogenations over Co-based materials 7,8,10,11 . However, it was recently shown that cobalt oxides could be the main phases responsible for the formation of hydrocarbons (mostly CH 4 ) over Co-based catalysts used for CO 2 hydrogenation 12 . The oxidation of a fraction of metallic cobalt could thus potentially be a major cause for the increased selectivity to methane when increasing the CO 2 proportions in CO-CO 2 -H 2 mixtures.…”
Section: Introductionmentioning
confidence: 99%
“…CoO is successfully used in catalytic processes of CO 2 hydrogenation [ 12 ], as photo- and electrocatalytic materials [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%